Thermally and Near-Infrared Light-Induced Shape Memory Polymers Capable of Healing Mechanical Damage and Fatigued Shape Memory Function - Li, Tianqi; Li, Yang; Wang, Xiaohan; Li, Xiang; Sun, Junqi (ACS applied materials & interfaces, 2019)
The fabrication of shape memory polymers that are mechanically robust and capable of being induced by near-infrared (NIR) light and healing mechanical damage and the fatigued shape memory function remains a challenge. In this study, thermally and NIR-light-induced shape memory polymers with self-healing ability and satisfactory mechanical robustness are fabricated by dispersing poly(acrylic acid) (PAA)-grafted graphene oxide (GO) (PAA-GO) into poly(vinyl alcohol) (PVA) matrix. The PVA/PAA-GO3% films with a PAA-GO content of 3.0 wt % have a fracture stress of ∼70.4 MPa and a Young’s modulus of ∼2.8 GPa. The PVA/PAA-GO3% films exhibit an excellent shape memory performance because PVA and PAA-GO form a stable network through hydrogen-bonding interaction between them. Meanwhile, the PVA/PAA-GO3% films are capable of recovering from temporary shape to permanent shape under NIR light irradiation because of excellent photothermal conversion property of the GO nanosheets. More importantly, benefiting from the reversibility of hydrogen-bonding interactions between PVA and PAA-GO nanosheets, the shape memory PVA/PAA-GO3% films are capable of healing physical damage and the fatigued shape memory function with the assistance of water, which greatly enhance their reliability as shape memory materials and prolong their service life.